Assessment of waterproofing failures in concrete buildings and structures - Othuman Mydin, Md Azree; Mohd Nawi, Mohd Nasrun; Che Munaaim, Muhammad Arkam (Construction Research Institute of Malaysia (CREAM), 2017)
This paper focuses on waterproofing failures in concrete buildings and structures.The objectives of this paper are three folds; (1) to determine the main factors that contribute to waterproofing failures in concrete buildings and structures (2) to discover different types of present waterproofing system applied for concrete buildings and structures (3) to propose remedial waterproofing solutions of concrete buildings and structures. There are 4 case studies were carried out at Cyberjaya, Malacca, Kuala Lumpur and Seremban.Each of them consist of different type of building namely SOHO (small office), Commercial building, Hotel Building and shopping mall.The results obtained shows that the main factors that contribute to waterproofing failures in concrete buildings and structure are cracks, deteriorated waterproofing system, honeycombs in concrete and construction joint failure.At the moment there are few types of present waterproofing system applied for concrete buildings and structures such as cementitious system, sheet membrane system and liquid system.Remedial waterproofing solutions of concrete building structures includes cleaning, removing old sealant or joint, injecting appropriate epoxy or chemical grout and applying a new layer of waterproofing system.